Impact of sacbrood virus on larval microbiome of apis mellifera and apis cerana - Rujipas Yongsawas (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. In this study, we examined the impact of Sacbrood virus (SBV), the cause of larval honeybee (Apis mellifera) death, producing a liquefied a larva sac, on the gut bacterial communities on two larval honeybee species, Apis mellifera and Apis cerana. SBV was added into a worker jelly food mixture and bee larvae were grafted into each of the treatment groups for 24 h before DNA/RNA extraction. Confirmation of SBV infection was achieved using quantitative reverse transcription polymerase chain reaction (RT-qPCR) and visual symptomology. The 16S rDNA was sequenced by Illumina sequencing. The results showed the larvae were infected with SBV. The gut communities of infected A. cerana larvae exhibited a dramatic change compared with A. mellifera. In A. mellifera larvae, the Illumina sequencing revealed the proportion of Gilliamella, Snodgrassella and Fructobacillus was not significantly different, whereas in A. cerana, Gilliamella was significantly decreased (from 35.54% to 2.96%), however, with significant increase in Snodgrassella and Fructobacillus. The possibility of cross-infection should be further investigated.